The South African Regulatory System: Past, Present, and Future - Keyter, Andrea; Banoo, Shabir; Salek, Sam; Walker, Stuart (Frontiers in Pharmacology, 2018)
The drive for improved regulatory systems and the establishment of a more effective regulatory framework in South Africa has been evident for the past two decades; but despite political intentions and legislative revisions, success has been limited to date. The promulgation of the recently amended Medicines and Related Substance Act of1965 triggered the establishment of the South African Health Products Regulatory Authority (SAHPRA), as a separate juristic person, outside of the National Department of Health, to replace the former medicine regulatory authority, the Medicines Control Council (MCC). The aim of this review is to provide the historical context supporting the new regulatory environment in South Africa and the transition from the MCC to SAHPRA. Key recommendations to SAHPRA to ensure the full potential of the new regulatory environment in South Africa, include establishing a quality management system to safeguard accountability, consistency and transparency and to streamline the implementation of good review practices including quality decision-making practices and benefit-risk assessment; the measurement and monitoring of regulatory performance, targets for overall approval time and key review milestones to instill a culture of accurate metrics collection and measurement of key performance indicators and their continuous improvement; and the employment of a risk-based approach to the evaluation of medical products and codify the use of facilitated regulatory pathways in policy and culture. The application of a risk-based approach to regulatory review commensurate with a product’s risk to patients will facilitate the application of increased resources for pharmacovigilance activities to support the reliance and recognition of reference agencies.